2017
DOI: 10.21307/sjcapp-2017-002
|View full text |Cite
|
Sign up to set email alerts
|

Child self-report and parent ratings for the Strengths and Difficulties Questionnaire: Norms and agreement in a Swedish random population sample

Abstract: Background: The Strengths and Difficulties Questionnaire (SDQ) measures behavioral problems among children and adolescents. Prior research in Sweden has included child self-report or parent ratings from community or population data. Objective: To provide child-reported and parent-rated SDQ norms for 11-to 16-year-olds, as well as data on child-parent agreement and parental sociodemographic correlates: education, employment status, and quality of life. Method: A random population sample with 600 children aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…Also, lack of recreational facilities and closed communities especially in rural Upper Egypt could play a role that increases the impact of the difficulties. This is in the same line with Liu et al, (4) who reported that females reported a higher negative impact of difficulties. On the contrary, Mowafy et al, (7) reported that there was higher significant impact of difficulties among students who had a working mother.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, lack of recreational facilities and closed communities especially in rural Upper Egypt could play a role that increases the impact of the difficulties. This is in the same line with Liu et al, (4) who reported that females reported a higher negative impact of difficulties. On the contrary, Mowafy et al, (7) reported that there was higher significant impact of difficulties among students who had a working mother.…”
Section: Discussionsupporting
confidence: 92%
“…However, epidemiological data on adolescent mental health problems in developing and Arab countries are limited. (4)(5) Adolescents' mental health problems are wide range of emotional and behavioral problems that range from minor difficulties to more severe ones that fulfill diagnostic criteria of a psychiatric classification. (3) They include depression, anxiety, adjustment, conduct, eating disorders and others.…”
Section: Introductionmentioning
confidence: 99%
“…Results from different subscales demonstrated that girls are more often affected by emotional problems, as well that they are better in social skills which is similar to other studies. On the other side, boys are more prone to peer relationship problems and have more conduct problems and that is also already recognized in the literature [4,[21][22][23]. In our study we found girls to have more hyperactivity/inattention problems, which is opposite to findings from other studies [21,23].…”
Section: Discussioncontrasting
confidence: 89%
“…Normative data available from the SDQ in the United States are limited to parent-reported SDQs, whereas the SDQs in this study were patient-reported. However, previous studies have shown relatively high parent-child agreement on SDQ measures, and the comparison between parent-and patient-reported SDQ measures was felt to be appropriate (20)(21)(22). Insufficient power due to small sample size likely limited our ability to detect differences in scores and detect relationships between SDQ scores and patient characteristics such as duration of disease.…”
Section: Discussionmentioning
confidence: 99%